2021
DOI: 10.18805/lrf-659
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Tissue Culture Regeneration System for Medicago ruthenica L. cv. ‘Zhilixing’

Abstract: Background: Medicago ruthenica L. ‘Zhilixing’ is a new variety with superior forage and seed yield compared to the wild type. The cold, drought and salt tolerance of Zhlixing are better than those of alfalfa, suggesting that this variety can serve as a high-quality genetic resource for improving the stress resistance of alfalfa. However, because of the lack of tissue culture regeneration system, it is difficult to perform genetic transformation studies on stress resistance genes. This study aimed to establish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The callus induction and differentiation rates, as well as shoot rooting rates, were analysed using analysis of variance (ANOVA, p< 0.05). The following evaluation indicators were calculated (Xu et al, 2022):…”
Section: Discussionmentioning
confidence: 99%
“…The callus induction and differentiation rates, as well as shoot rooting rates, were analysed using analysis of variance (ANOVA, p< 0.05). The following evaluation indicators were calculated (Xu et al, 2022):…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of exogenous growth hormones to cytokinins controls plant regeneration in isolates and regulates the internal and external balance by influencing endogenously produced phytohormones (Xu et al 2022). It has been shown that different phytohormones have different abilities to detect receptor protein target cells and that different combinations of hormones alter the induction and proliferation of repair tissues .…”
Section: Effect Of Exogenous Hormones On the Activation Of Healing Ti...mentioning
confidence: 99%
“…W ith its wide ecological adaptability, rich nutritional value and high-stress tolerance (Liu et al, 2013), as well as its high strain variation and high intraspecific genetic diversity, some studies have shown that lentil beans can provide valuable genes for genetic improvement of Medicago sativa (Wang et al, 2008). Medicago ruthenica can be used as a high-quality genetic resource for improving the stress resistance of alfalfa and other pastures (Xu et al, 2021). Transcriptomics is currently the most direct and universal way to study genome-level changes (Jing et al, 2016), which broadly refers to the study of the abundance of all the RNA transcripts of an organ or tissue under a particular condition.…”
Section: Introductionmentioning
confidence: 99%